Conscientiousness and Smoking: Do Cultural Context and Gender Matter? - Lee, Chioun; Gao, Manjing; Ryff, Carol D. (Frontiers in Psychology, 2020)
Prior studies have found that conscientiousness has a protective effect against smoking, but evidence for this relationship mostly comes from Western contexts. In societies where smoking is pervasive and less stigmatized, the protective effect of conscientiousness on smoking may be less evident. Moreover, whether smoking is viewed as normal or deviant also may vary by gender norms attached to smoking. Using surveys of Midlife Development in the US (MIDUS) and Japan (MIDJA), we examined patterns in the association between conscientiousness and smoking status (never, former, current) for men and women. We found that in the US, where the social unacceptability of smoking has dramatically increased, there is an inverse association between conscientiousness and smoking status for both genders. In Japan, where the stigma attached to smoking operates for women but not men, the association between conscientiousness and smoking status varies by gender. For Japanese men, levels of conscientiousness do not differ across smoking statuses. For Japanese women, those who formerly smoked show lower levels of conscientiousness than those who never smoked and those who currently smoke. We interpret these findings in light of differing cultural and historical backgrounds of smoking for men and women.